TIPOLOGI GURU SEJARAH PADA PEMBELAJARAN ABAD KE-21 (Kajian Grounded Theory di SMA) - Ema Agustina, - (2022)
The type of history teachers should be more heterogeneous and more varied in 21st century learning. This study aimed to formulate the types of history teachers based on the characteristics of history learning function and the characteristics of 21st century learning. This study used grounded theory. 10 history teachers in Indonesian secondary schools participated by using theoretical sampling techniques. The data were collected from several literatures, interviews, and observations. Open coding, axial coding, and selective coding were applied as the data analysis. The results revealed that:1) there found conservative, normative, inspirative, imaginative, and innovative types of history teachers; 2) those formulated typologies were considered from students' motivation, teaching materials, teaching styles, students' roles, and evaluation. It was found that the conservative teachers have not been capable of boosting students' motivation. The evidence showed the limited use of other learning sources instead of textbooks, teaching media, and students' roles. The normative and inspirative teachers have triggered students' motivation but it had to be kept stimulating and developing the materials. The normative and inspirative teachers had infused various media and learning sources. The imaginative and innovative teachers had pushed students' motivation greatly and developed teaching materials. They also infused more varied learning sources, media, and teaching styles; 3) conservative teachers have not been implementing 21st century learning. Meanwhile, the normative and inspirative teachers had been implementing 21st century learning but it needed to enhance 4Cs skills, ICT-based teaching, and varied blended learning. Imaginative and innovative teachers had been ready and capable to implement 21st century learning.